The academic journey of students with specific learning difficulties undertaking pre-registration nursing programmes in the UK: A retrospective cohort study. (April 2022) - Crawford, Caroline; Black, Pauline; Melby, Vidar; Fitzpatrick, Ben
Abstract: Background: The prevalence of nursing students with specific learning difficulties enrolled on pre-registration nursing programmes and the impact that this diagnosis has on their programme outcomes are currently unknown. Objectives: The aim of this paper is to report on data that explored and compared the academic journey of students with and without learning difficulties on pre-registration nursing degree programmes. Design: A retrospective cohort design. Settings: One university in the UK offering BSc Honours Degree programmes in Adult and Mental Health Nursing. Participants: Pre-registration adult and mental health nursing students ( n = 1152) enrolled in the programmes between 2012 and 2016. Methods: Pearson's Correlation, ANOVA and crosstabulation were used to identify the differences and associations between each group of students with the outcome variables grade percent average and programme completion. Results: A total of 12.5% of the students were identified as having a diagnosed specific learning difficulty and were entitled to reasonable adjustments. The analysis shows that their grade percent average and completion rates are equivalent to students without a specific learning difficulty. Conclusions: The differences between students with a specific learning difficulty and those without are small across the variables measured. Reasonable adjustments appear to mitigate the learning difficulties that students with specific learning difficulties have. Educators need to continue to promote ways of identifying students with specific learning difficulties as early as possible in the student's academic journey. Responsive adjustments in teaching and assessment in theory and practice components should be implemented to ensure that all students' opportunities to succeed are maximised.